Analyzing The Easing of Japan’s Arms Disarmament Policy Between 2010-2020 - Iswari, Rani Dian; Musyaffa, Nadhif Fadhlan (Global Strategis, 2025)
Arms disarmament policy is widely implemented among countries in the world, especially after the Cold War era. On the other hand, the Japanese Government's policy in easing disarmament arms policy has become a new 'way' in Japan's military ideology since its loss in World War II and was forced to implement pacifism. This study uses the defensive realism theory to explain why Japan eased its arms disarmament policy from 2010 to 2020 under three prime ministers. This research was conducted using qualitative methods using primary data from ministries and departments of Japan and secondary data from scientific journals, books, theses, newspaper articles, and websites. The study results show that easing Japan's disarmament policy is a form of action to maintain the balance of power, especially to balance the aggressiveness of the People's Republic of China (China) and the Democratic People's Republic of Korea (North Korea) in terms of military. Keywords: balance of power, Japan's arms disarmament policy, Japan’ military, policy loosening/easing Kebijakan perlucutan senjata banyak diterapkan oleh negara-negara di dunia, terutama setelah era Perang Dingin. Di sisi lain, kebijakan Pemerintah Jepang dalam melonggarkan kebijakan perlucutan senjata menjadi 'cara' baru dalam ideologi militer Jepang sejak kekalahannya dalam Perang Dunia II dan terpaksa menerapkan pasifisme. Penelitian ini menggunakan teori realisme defensif untuk menjelaskan mengapa Jepang melonggarkan kebijakan perlucutan senjatanya pada tahun 2010 hingga 2020 di bawah tiga perdana menteri. Penelitian ini dilakukan dengan metode kualitatif dengan menggunakan data primer dari kementerian dan departemen di Jepang dan data sekunder dari jurnal ilmiah, buku, tesis, artikel surat kabar, dan website. Hasil kajian menunjukkan bahwa pelonggaran kebijakan perlucutan senjata Jepang merupakan salah satu bentuk tindakan untuk menjaga keseimbangan kekuatan, terutama untuk menyeimbangkan agresivitas negara Republik Rakyat Tiongkok (Tiongkok) dan Republik Demokratik Rakyat Korea (Korea Utara) dalam hal militer. Kata-kata Kunci: keseimbangan kekuatan, kebijakan perlucutan senjata Jepang, militer Jepang, pelonggaran kebijakan